Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Dengan Menggunakan Metode Cooperative Integrated Reading And Composition (CIRC) Pada Peserta Didik Kelas IV-A SDN 6 Menteng Tahun Pelajaran 2022/2023 - Rosalia Septia Gresheilla; Femmy Femmy; Simpun Simpun; Diplan Diplan (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This research is motivated by the lack of learning outcomes in Indonesian at grade IV-A SDN 6 Menteng and the use of methods that are still one-way. The aims of the study were to describe (1) the improvement of student outcomes (2) teacher activities (3) student activities in learning Indonesian one-point chapter 6 at SDN 6 Menteng using the Cooperative Integrated Reading and Composition method (CIRC). This research is a Classroom Action Research model by Kemmis and Mc. Taggart that was carried out in 2 cycles. The research subjects are 22 students. The data collection techniques, namely observation and tests using quantitative and qualitative data analysis techniques. The results of this Research show that using the Cooperative Integrated Reading and Composition method (CIRC) can improve learning outcomes and learning activities. This is based on the research results on the pretest and pre-cycle data with an average of 59.09 with a classical value of 31.81%. Cycle I average score of 68.18 and classical value of 68.18% with the activities of teachers and students in the good category. In cycle II the average value increased to 89.54 and the classical value was 100% with very good teacher and student activities. Therefore learning outcomes have increased by 21.36.